(untitled) (Journal of Nepal Geological Society, 2011)
Determination of in-situ stresses in the rock mass is necessary for stability assessment and proper design of underground openings. It is important to know the state of stress surrounding the opening so that right and optimum rock support is assigned as preliminary and permanent rock support. However, the majority of long tunnels with high rock cove r face severe tunnel instability problems related to rock stresses. The headrace tunnel of Parbati II hydroelectric project is one of such tunnels, especially the tunnel segment passing through Manikaran quartzite. It is known fact that the extent and type of stress induced instability vary greatly upon rock type, deformability properties, jointing and inter-bedding characteristics in the rock mass. This paper back calculates the state of stress using Phase 2 finite element model in a TBM bored segment of the tunnel and also briefly reviews mechanical properties of the intact rock that may have direct link on the nature of stress induced instability. It is believed that back calculated stress magnitude may be useful for the stability assessment in other segment of headrace tunnel.